J. M. Castellet and Existentialism - Vall, Xavier (Tropelías: Review of Literary Theory and Comparative Literature, 1999)
Although J. M. Castellel had previously written on authors assigned to this tendency, the existencialist influence -which himself recognizes that was considerable- took root fully in his work from reading, in 1950, an Argentinian translation of Qu'est-ce que la littérature?, by Sartre, and it is particularly evident along this decade, though it will persist, mixed with other stimulli (such as Marxism and Structuralism). Following the pattern of Sartre and other ones, but adapting them skilfully to his personality and of the peculiar Hispanic circumstances, Castellet has based his literary theory on the commitment of the writer, on Objetivism and on the appeal to the reader, and has interpreted and valued works with regard of the "situation" and according to the "revelation of lhe world", in which he has believed inherent the use of modern forms.
Keywords: J. M. Castellet; Jean-Paul Sartre; existentialism